A CBCT study on distolingual space of mandibular molars in adults with different sagittal skeletal patterns - LI Zongfeng, SUN Lian, PAN Yongchu (Editorial Office of Stomatology, 2024)
Objective To study the distolingual space of mandibular molars in adult patients with different sagittal skeletal patterns, and to analyze the main bony anatomical sites that restrict molar distalization, in order to provide guidance for the treatment plan of molar distalization. Methods A total of 97 adult patients according to the inclusion criteria were selected from the Department of Orthodontics, the Affiliated Stomatological Hospital of Nanjing Medical University.The patients were divided into skeletal Class Ⅰ group(n=28), skeletal Class Ⅱ group(n=49) and skeletal Class Ⅲ group(n=20) according to the ANB angle. CBCT of the patients were imported into Dolphin software for 3D reconstruction. The width of the distal root of the second molar, the width of alveolar bone, the distance between the most convex point of the distal and lingual side of the distal root and the inneredge of the lingual cortex of the mandible were measured at the 2, 4, and 6 mm plane from the root furcation to the root apex. Statistical analysis was performed using SPSS 26.0 software, and univariate analysis of variance and LSD-t test were used to compare the difference. Results Root width was significantly narrower than alveolar bone width at all measurement planes(P<0.01). Molar distolingual space in patients with different sagittal skeletal patterns was smaller than molar distal space, and the size of the space gradually decreased with the deepening of the measurement level, reaching the minimum value at the R4 and R6 measurement planes. Measurement results of this study showed that at the R6 level, the molar distolingual space in skeletal Class Ⅱ group was the minimum (2.30±2.45)mm; on the contrary, skeletal Class Ⅲ group was the maximum (4.17±2.38)mm. Conclusion When designing the plan of molar distalization in clinical practice, CBCT should be used, and more attention should be paid to the lingual alveolar bone mass of the mandibular molar. It is a safe and effective treatment method for skeletal Class Ⅰ and Ⅲ patients with mild to moderate dental crowding.